Potensi Spons sebagai Media Alternatif Budidaya Sayuran dengan Sistem Hidroponik - Tati Barus; Adrina Weisa; Renna Eliana Warjoto (Perkumpulan Agroteknologi/Agroekoteknologi Indonesia, 2021)
Several technologies are evolving with the increasing agricultural product demand. The use of hydroponic systems appears more common, where the growing medium serves as a significant factor in determining plant growth, without available information on the use of sponges. This study is aimed at obtaining information on the potential of sponges as a hydroponic media in water spinach (Ipomoea aquatica), pak choi (Brassica rapa) and kale (Brassica oleracea). The method used was a completely randomized design with three replications and the treatment comprised of three growing media types, termed sponges, local and imported rockwool. The result showed an improvement in the growth of water spinach and pak choi in sponges, compared to local and imported rockwool. Furthermore, kale was known to develop more extensively on the entire media but varied insignificantly in kale.